First detection of Echinococcus granulosus G1 and G7 in wild boars (Sus scrofa) and red deer (Cervus elaphus) in Romania using PCR and PCR-RFLP techniques - Onac, D.; Győrke, A.; Oltean, M.; Gavrea, R.; Cozma, V. (Veterinary parasitology, 2013)
The epidemiological status of CE in our country places Romania into the top of the European countries and among the first countries worldwide. Two hundred ninety wild animals (267 wild boars, 21 red deer and 2 mouflons) hunted in a private ground from Bihor county from western Romania were the subject of the necropsy in January 2012.Out of 290 wild animals, 35 were positive during necropsy for hydatic cysts and from these, 33 wild boars and 2 red deer had hydatic cystsonly in the liver parenchyma. This paper presents the first identification of Echinococcus granulosus G1 in cervids (100%). In wild boars it were identified G1 (45.5%) and G7 genotypes (39.4%). The mouflons were free of hydatic cysts. Our resultsconfirmthat the sheep strain (G1) is the predominant Echinococcus genotype, which occurs, followed closely by the pig strain (G7) and that wildlife reservoirs should be taken in consideration for the management of the disease.